2022
DOI: 10.3390/diagnostics12081975
|View full text |Cite
|
Sign up to set email alerts
|

Automated Diabetic Retinopathy Detection Using Horizontal and Vertical Patch Division-Based Pre-Trained DenseNET with Digital Fundus Images

Abstract: Diabetic retinopathy (DR) is a common complication of diabetes that can lead to progressive vision loss. Regular surveillance with fundal photography, early diagnosis, and prompt intervention are paramount to reducing the incidence of DR-induced vision loss. However, manual interpretation of fundal photographs is subject to human error. In this study, a new method based on horizontal and vertical patch division was proposed for the automated classification of DR images on fundal photographs. The novel sides of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Table 1 summarizes the many attempts to detect DR anomalies in photos using various DL techniques [17,21,[26][27][28][29][30][31][32]. According to the results of the research into DR identification and diagnostic methods, there are still a lot of loopholes that need to be investigated.…”
Section: Related Workmentioning
confidence: 99%
“…Table 1 summarizes the many attempts to detect DR anomalies in photos using various DL techniques [17,21,[26][27][28][29][30][31][32]. According to the results of the research into DR identification and diagnostic methods, there are still a lot of loopholes that need to be investigated.…”
Section: Related Workmentioning
confidence: 99%
“…Subsequent study in areas of medicine opened the way for the development of numerous computer-assisted technologies, including data mining, image processing, ML, and DL. In recent years, DL has received attention in numerous disciplines, including sentiment classification, handwriting identification, and healthcare imaging analysis [12,13], among others fields [7].…”
Section: Of 15mentioning
confidence: 99%
“…Several research has been done to identify and classify DR at various stages simultaneously. Traditional image processing and DL both have their place in such picture categorization challenges [7,[27][28][29][30][31][32]. The investigation on DR identification and diagnostic methods showed that there continue to be a number of flaws that have to be reviewed.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations